Jerusalem in Viken: crusading ideology, church-building and monasticism in south-eastern Norway in the twelfth century - Bandlien, Bjørn (Cappelen Damm Akademisk, 2023)
St Olav's Church in Tønsberg in Viken (the area surrounding the Oslo Fjord in south-eastern Norway) burned along with most of the medieval town in 1536, the same year the Reformation was introduced to Norway. The church was never rebuilt, and its ruins were forgotten for centuries. When they were finally uncovered in the late nineteenth century, scholars realized that this was by far the largest round church built in medieval Scandinavia. Later excavations have revealed that this church was erected in the late twelfth century and became a part of a Premonstratensian foundation. However, the scarcity of written records has left many questions open for debate - such as the identity of the founder and the intentions behind its construction. The contributors to this anthology look at the material and textual evidence afresh, from different starting points and perspectives. Most importantly, St Olav's Church is seen in connection with both the introduction of the Hospitallers to Varna just across the Oslo Fjord, and with the other round churches or rotundas in Scandinavia. Several chapters discuss the foundation of the church in light of the political and religious context in Viken, as well as Norwegian participation in the crusading movement in the twelfth century, and in this way, the building of St Olav's Church can be seen as a monumental example of the attempts to imitate the Church of the Holy Sepulchre in Jerusalem and associate the region with a holy topography. With the publication of Jerusalem in Viken: Crusading Ideology, Church-Building and Monasticism in South-Eastern Norway in the Twelfth Century, these important sites are presented to an international audience for the first time. The book will be useful to scholars - and the general reader - interested in round churches, the crusading movement, religious culture, the Premonstratensian order, and relations between Scandinavia and Europe in the Middle Ages